2014
DOI: 10.14737/jimb.2307-5465/2.4.49.52
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Diseases in Camels of Cholistan Desert, Pakistan

Abstract: An epidemiological study was executed to determine the prevalence of common diseases in camels of Cholistan desert, Pakistan. Starting from Fort Abbas to Rahim Yar Khan, the survey was carried out from May 2010 to April 2011. Epidemiological data was collected from the camel herds of Cholistan (Locally called as Tobbas) and analyzed to interpret current scenario of camel diseases. The overall prevalence of all diseases in camels was 15.8%. The prevalence of trypanosomiasis, pneumonia, mange, and anthrax in cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
3
8
2
Order By: Relevance
“…Furthermore, our present results are not consistent with previous reports in domestic animals, such as cattle, and wild animals, such as Iberian wolves and cheetahs, that reported a higher prevalence in young animals [42]. Meanwhile, another previous study has stated that both very young and aged camels are mostly liable [43]. It is noteworthy to state the fact that young camels are usually kept indoors under intensive rearing while older ones participate in work and grazing that might justify the higher susceptibility of older animals than younger ones [35].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our present results are not consistent with previous reports in domestic animals, such as cattle, and wild animals, such as Iberian wolves and cheetahs, that reported a higher prevalence in young animals [42]. Meanwhile, another previous study has stated that both very young and aged camels are mostly liable [43]. It is noteworthy to state the fact that young camels are usually kept indoors under intensive rearing while older ones participate in work and grazing that might justify the higher susceptibility of older animals than younger ones [35].…”
Section: Discussioncontrasting
confidence: 99%
“…However, a previously published report detected a similar infestation rate of mange in male and female sheep [41]. Several studies documented the impact of seasonality on camel mange [12,23,24,29,37,43]. Among others, one study demonstrated that camel mange is more prevalent in summer than winter [43], while the remaining studies reported the opposite, a higher prevalence of mange in winter than summer, which is consistent with our present findings [21,23,29,37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This value is higher than the figure in Awol et al [22], Dinka et al [1], Lawal et al [23] and Chaudhry et al [24] who reported 16.7, 10.7, 3.5 and 3.14 % prevalence from Northern Ethiopia, Eastern Ethiopia, Sokoto-Nigeria and Cholistan-Pakistan, respectively and lower than a prevalence of 83 % reported by Al-ani et al [25] in Jordan. Variation in genetics, environment, accessibility to veterinary services, herd size and other husbandry practices could justify these differences.…”
Section: Discussioncontrasting
confidence: 59%
“…On prevalence of mange on sex of camel's different authors had different opinions; some stated that camels male is more affected by mange than female [32]. Others however, stated female are more affected than male [1,[38][39][40]. This may be associated with some hormonal influences; the higher level of prolactin and progesterone hormones could make the females more susceptible to any infection [41].…”
Section: Risk Factor Of Camel Mangementioning
confidence: 99%